Region-building in southern Africa : progress, problems and prospects - Sanders, Chris; Dzinesa, Gwinyayi A.; Nagar, Dawn (Zed Books, 2012)
How successful have southern African states been in dealing with the major issues that have faced the region in recent years? What can be done to produce more cohesive and effective region-building in southern Africa? This original and wide-ranging volume, which draws on an interdisciplinary team of African and African-based specialists, addresses the key political, socio-economic and security challenges facing southern Africa today.